Defending Environmental Economic Instruments against the Economists and their Opponents: Analysing the Major Tool of Transformation to Sustainability - Ekardt, Felix (Momentum Quarterly, 2016)
Both advocates and opponents of economic instruments in environmental policy base their opinions on neoclassical economics, which they then either welcome or criticize. This paper aims to show that economic instruments are still (or especially) effective policy approaches for transformation towards sustainability, if assuming that those basic assumptions are wrong. This applies to six focal points: (1) the role of technical innovation and sufficiency; (2) the role of economic (de-)growth; (3) the role of cost-benefit analysis; (4) overestimated cost efficiency and under-estimated potential to solve crucial governance challenges; (5) the misleading debate on homo oeconomicus; (6) the forgotten potential of economic instruments to address different environmental issues at the same time.
Keywords: economic instruments; economic evaluation; cost-benefit analysis; sustainability; climate protection